(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
In support of ongoing educational transformation in post-Soviet nations, this article positions activity theory (in the tradition of Engeström) as a framework for modelling changes towards innovative forms of collabo-rative, fully online digital learning. A strength of activi-ty theory is that it adopts a holistic socio-technical per-spective in which teachers, learners, technologies, peda-gogical values, roles/identities and rules/cultures are considered together as interdependent elements of col-lective activity. An illustrative example is offered to model a current and envisioned (target) activity system. In addition, a few considerations to guide research are offered. These include an emphasis on measuring the general readiness of students and teachers, and the need to explore gender divides. The goal is to help envision program transformations towards online learning at two partner universities as part of Ukrainian and Lat-vian, government-funded projects.